Olfactory neuroblastoma: A peculiar case showing unusual squamous metaplasia in a late lymph node metastasis - Hiroshi Harada; Takeharu Ono; Takanori Hirose; Hirohito Umeno; Jun Akiba; Akira Kurose (Elsevier, 2022)
Olfactory neuroblastoma is a rare neuroendocrine tumor derived from the olfactory epithelium. We report a case that showed peculiar histology in a late lymph node metastasis. The patient was a 78-year-old Japanese male, who had headache, epistaxis, and nasal obstruction following bloody sputum that was untreated for ten years. The initial biopsy was interpreted as anaplastic carcinoma, and after being referred to a regional university hospital, a total of 60 Gy of radiation therapy was performed prior to the excision of the residual tumor. Neck metastasis was found on the left side two years later, and the patient died of other disease with no recurrence five years after successful neck dissection.Retrospective examination of the biopsy specimen revealed a neurofibrillary matrix besides nesting growth of basophilic naked cells. The neck metastases exhibited similar histology, and a large number of rosette structures containing mucus and extensive squamous metaplasia were observed. Immunohistochemically, naked cells and neurofibrillary matrix were positive for synaptophysin and chromogranin A, and rosette structures and some naked cells were positive for AE1/AE3 and CAM5.2. While epithelial differentiation of olfactory neuroblastoma is a unique feature absent in neuroblastomas in other regions, it was clearly and prominently manifested in the present case.